2009
DOI: 10.1182/blood-2008-11-189399
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation in children and adolescents with recurrent and refractory Hodgkin lymphoma: an analysis of the European Group for Blood and Marrow Transplantation

Abstract: Ninety-one children and adolescents 18 years or younger after allogeneic hematopoietic stem cell transplantation (HSCT) for relapsed or refractory Hodgkin lymphoma (HL) were analyzed. Fifty-one patients received reduced intensity conditioning (RIC); 40 patients received myeloablative conditioning (MAC). Nonrelapse mortality (NRM) at 1 year was 21% (؎ 4%), with comparable results after RIC or MAC. Probabilities of relapse at 2 and 5 years were 36% (؎ 5%) and 44% (؎ 6%), respectively. RIC was associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 28 publications
3
42
0
3
Order By: Relevance
“…The best conditioning protocol is unknown, although information from registry analyses indicates that the intensity of the conditioning regimen matters. In children and adolescents, the use of myeloablative protocols was not associated with higher NRM but significantly reduced the relapse incidence as compared to RIC protocols 29 The use of low dose total body irradiation (2 Gy) seems to be associated with a higher incidence of relapse and a lower progression-free survival. 16,19 Accordingly, enforcing the debulking of the tumor by adding further drugs or otherwise strengthening the anti-tumor effect may help to reduce the relapse rates after allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best conditioning protocol is unknown, although information from registry analyses indicates that the intensity of the conditioning regimen matters. In children and adolescents, the use of myeloablative protocols was not associated with higher NRM but significantly reduced the relapse incidence as compared to RIC protocols 29 The use of low dose total body irradiation (2 Gy) seems to be associated with a higher incidence of relapse and a lower progression-free survival. 16,19 Accordingly, enforcing the debulking of the tumor by adding further drugs or otherwise strengthening the anti-tumor effect may help to reduce the relapse rates after allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%
“…These patients might benefit from more aggressive conditioning and/or changing the GVHD prophylaxis. 29 The progression-free survival rate was 48% (95%CI, 44-52) at 1 year and 24% (95%CI, 22-27) at 4 years for the allografted population. The figures are significantly better for patients allografted with chemosensitive disease and particularly for patients allografted in complete remission.…”
Section: Discussionmentioning
confidence: 99%
“…Allojenik nakillerde de nakil sırasındaki hastalık durumunun sonucu belirleyen en önemli prognostik faktör olduğu gösterilmiştir. Yakın zamanda yapılan EBMT çalışmasında allojenik nakil sonrası 2 ve 5 yıllık genel sağkalım oranları %54 ve 45 olarak belirtilmiş ve düşük yoğunluklu hazırlama rejimi verilenlerde relaps oranlarının daha fazla ve progresyonsuz sağkalımın daha düşük olduğu bulunmuştur 7 .…”
Section: Hodgkin Lenfomaunclassified
“…However, it has been observed that event-free survival is better in lymphoblastic lymphoma subtype with allogeneic transplantation (4% vs. 40%). Although acceptable results are obtained with allogeneic transplantation in cases of relapse and in refractory patients in Hodgkin lymphoma, relapse is still the most important cause of treatment failure (33).…”
Section: Lymphomamentioning
confidence: 99%